Factor VIIa and tissue factor procoagulant activity in diabetes mellitus after acute ischemic stroke: Impact of hyperglycemia - Gentile, Nina T.; Vaidyula, Vijender R.; Kanamalla, Uday; De Angelis, Michael; Gaughan, John; Rao, Koneti A. (Thrombosis and Haemostasis, 2007)
Alterations in blood coagulation may explain the poorer neurological outcome with diabetes mellitus and hyperglycemia after acute ischemic stroke. We studied the relationships between diabetes mellitus, hyperglycemia, whole blood tissue factor procoagulant activity (TF-PCA) and plasma Factor VIIa (FVIIa) in ten patients with type 2 diabetes mellitus and 11 non-diabetic patients at baseline and 6, 12, 24, and 48 hours (h) after presentation for acute stroke. In addition, we examined plasma prothrombin fragment 1+2 (F1.2) and thrombin-antithrombin complexes (TAT) as markers of thrombin generation. Stroke severity, assessed by National Institute of Health Stroke Scale (NIHSS), was similar at baseline (p=0.26) but worse in diabetic (8.20 ± 4.3) than nondiabetic patients (2.67 ± 2.1,p=0.023) at 48 h. At presentation, diabetic patients had higher FVIIa (p=0.004) and lower TF-PCA (p=0.027) than non-diabetic patients but both were higher than in normal control subjects. FVIIa levels remained higher in diabetic patients at 6, 12 and 24 h after stroke. In diabetic patients, FVIIa (r=0.40, p=0.02) and TF-PCA (r=0.50, p=0.02) correlated with blood glucose; and, FVIIa correlated with plasma F1.2 (r=0.34, p=0.002) and TAT levels (r=0.62, p<0.0001). In non-diabetic patients, TF-PCA, but not FVIIa, correlated with F1.2 (r=0.402, p=0.010) andTAT (r=0.39, p=0.011). Combining both groups, NIHSS scores were positively related to FVIIa levels (r=0.50,p=0.021) and inversely related toTF-PCA levels (r=-0.498, p=0.02). Acute ischemic stroke patients with diabetes and hyperglycemia have a more intense procoagulant state compared with nondiabetic patients. This is related to glucose levels and provides a potential mechanism for the observed worse prognosis in such patients after acute stroke.
Keywords: Stroke; diabetes; hyperglycemia; procoagulant state; tissue factor